Water absorption hydrogel agricultural use and wetting of three soil types - Rivera Fernández , Rubén Darío; Gallo, Freddy Mesías (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
The objective was to evaluate the percentage of water absorption and wetting in three soil types. It was used as experimental material to Acrylamide Polymer Potassium (PAP) and three floors of sand, loam and clay type. The amount of water (mL) and time (minutes) which absorbs 1g of PAP was measured. In addition, the wetting of PAP for each soil type by placing 1 g dry soil was evaluated previously soil moisture was measured before and after placing the PAP. The results indicate that the hydrogel absorbed per gram PAP about 103 mL, this absorption is increasing function of time reached, after this time turning point at 60 min the increase is not significant. It wetting had a variable increase depending on the type of soil, being 14.7, 17.4 and 14.5% for sand, loam and clay soils respectively. This wetting is obtained after about an hour. In saturated soil gels remain unchanged. However in a dry soil, the gels gives the contained water to the ground becoming part of the soil`s water.